Bamboo consumption and health outcomes: A systematic review and call to action - Pizzol D.; Zampieri T.; MacKinnon R.; Yon D. K.; Richardson F.; López Sánchez G. F.; Caminada S.; Bertoldo A.; Butler L.; Veronese N.; et al. (My University, 2025)
Despite the popularity and potential nutritional benefits of bamboo consumption in aiding the prevention and management of several health conditions, to date, no attempt has been made to collate and critically appraise all literature on bamboo and human health. We aimed to address this gap in the literature through a systematic review. We systematically searched Medline/PubMed and Web of Science electronic databases until 26th October 2024. All retrospective or prospective studies reporting the effects of human consumption of bamboo shoots or other bamboo products on health were included. In vitro findings related to the effect of bamboo extracts on human cells or in processing food were also included. In vivo studies demonstrated a protective effect against internal exposure to acrylamide and glycidamide, an improvement in glycemic control, improvement in lipid profile, improvement in bowel function, an increase in antioxidant and anti-inflammatory activity, a lower cell toxicity and increased cell viability but also an association with a high prevalence of goiters. In vitro studies demonstrated antioxidant activity, probiotic effects, inhibition of furan formation, high nutritional value and reduction of acrylamide formation during food processing. The findings from our systematic review, which included 16 studies, suggest that if appropriately prepared, the consumption of bamboo may have multiple health benefits for humans. However, more high-quality experimental trials are required to further elucidate on the health benefits before concrete recommendations can be drawn. We thus call on the academic community to further investigate this crop for its high potential for improving human health.
Keywords: Tarımsal Bilimler; Ormancılık; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Forestry; Environmental Engineering; Engineering and Technology; Tarım ve Çevre Bilimleri (Age); Bitki ve Hayvan Bilimleri; Çevre / Ekoloji; Çevre Bilimleri; Agriculture & Environment Sciences (Age); Plant & Animal Science; Environment/Ecology; Environmental Sciences; Yaşam Bilimleri; Çevre Bilimi (çeşitli); Fizik Bilimleri; Life Sciences; Environmental Science (miscellaneous); Physical Sciences; Bamboo; Bamboo extracts; Bamboo shoots; Food; Nutrition